Pemutakhiran Pengembangan Produk Menggunakan Kerangka kerja “Integrated Conceptual Selection (ICS)” - Nanang Fatchurrohman; M. Ilham Adelino; Meldia Fitri (Universitas Putra Indonesia YPTK Padang, 2021)
In today’s overwhelming competition, the knowledge on product development represents a very significant aspect for companies to survive in the market. Among these sectors is the automotive industry, where it is one of the fastest growing, highly demanding and stiff competition marketplaces. Intensive research in this field is targeted to produce light weight and high-performance components which can increase fuel efficiency and sustainability of an automobile. One of the recent avenues is the investigation of increased performance engineered materials to replace the conventional materials. In this study product development of engineered material - component is explored. To achieve a sound product development, new integrated product development framework which utilized simultaneous approach is developed. The framework is referred to as Integrated Conceptual Selection (ICS) which streamlines the phases in the product development process, including product investigation, product specification and conceptual design.